Development and Performance of the Pepper Industry in Malaysia: A Critical Review - Harry Entebang; Swee-Kiong Wong; Zehnder Jarroop Augustine Mercer (International Journal of Business and Society, 2020)
The National Commodity Policy 2011-2020 was developed to increase the national income by harnessing the potential of commodity export revenues. Despite continuous efforts implemented by various related agencies, the overall performance of major commodities, particularly pepper, remains unsatisfactory. Regarded as a sought-after ‘king of spices’, pepper has become one of the most prized and important commodities traded globally. This paper highlights the development and performance of the pepper industry in Malaysia and discusses practical strategies and recommendations to transform the pepper industry. Besides conducting interviews with the industry experts to gain first-hand information, content and thematic analysis was employed based on secondary data research in this study. The findings of the study show that even though pepper is mostly used in food-related industries, its potential in pharmaceutical and cosmeceutical sectors remains underexplored. Globally, the overall supply and demand of pepper continue to increase, though the demand has recently exceeded supply. However, continuous new planting and farm expansion initiatives by major producers caused the total global pepper supply to exceed consumption in 2018. In fact, pepper prices have declined more than 70% since 2015, which affected the overall household income of the rural community engaged in pepper farming. While experiencing low prices, smallholder pepper farmers and the industry continue to struggle with low domestic consumption, low production, higher cost of farm inputs, lack of extension services, low impact of research, development and innovation, ageing farming population, intense competition from other producing countries, low prices for quality pepper, limited subsidy to support continuous farming, pepper-related diseases, lack of new technology, and poor investment in downstream activities. Given this, the performance of the Malaysian pepper industry has fallen below expectations.